2011
DOI: 10.1093/jxb/err320
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that abscisic acid promotes degradation of SNF1-related protein kinase (SnRK) 1 in wheat and activation of a putative calcium-dependent SnRK2

Abstract: Sucrose nonfermenting-1 (SNF1)-related protein kinases (SnRKs) form a major family of signalling proteins in plants and have been associated with metabolic regulation and stress responses. They comprise three subfamilies: SnRK1, SnRK2, and SnRK3. SnRK1 plays a major role in the regulation of carbon metabolism and energy status, while SnRKs 2 and 3 have been implicated in stress and abscisic acid (ABA)-mediated signalling pathways. The burgeoning and divergence of this family of protein kinases in plants may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 54 publications
4
58
0
Order By: Relevance
“…This is in agreement with a recent study reporting enhanced SnRK1 activity in wheat (Triticum aestivum) roots in response to ABA (Coello et al, 2012), and provides a molecular explanation for the extensive interactions observed between ABA and sugar signaling in genetic screens (Rolland et al, 2006). SnRK1s were never identified among ABA-activated kinases, most probably because the extent of SnRK1 activation by ABA is 1 order of magnitude lower than that by energy stress (Darkness; Figure 5B), and would probably remain masked by the much stronger activities of SnRK2s.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with a recent study reporting enhanced SnRK1 activity in wheat (Triticum aestivum) roots in response to ABA (Coello et al, 2012), and provides a molecular explanation for the extensive interactions observed between ABA and sugar signaling in genetic screens (Rolland et al, 2006). SnRK1s were never identified among ABA-activated kinases, most probably because the extent of SnRK1 activation by ABA is 1 order of magnitude lower than that by energy stress (Darkness; Figure 5B), and would probably remain masked by the much stronger activities of SnRK2s.…”
Section: Discussionsupporting
confidence: 94%
“…The Arabidopsis thaliana genome encodes 38 SnRKs, of which three, SnRK1.1 (KIN10/AKIN10), SnRK1.2 (KIN11/AKIN11), and SnRK1.3 (KIN12/AKIN12), represent the orthologs of the budding yeast (Saccharomyces cerevisiae) sucrose-nonfermenting1 (Snf1) and mammalian AMP-activated protein kinase (AMPK) metabolic sensors (Halford et al, 2003;Polge and Thomas, 2007;Hardie, 2011). An increasing body of evidence suggests that SnRK1s act as convergence points for various metabolic, hormonal and stress signals during growth and development, linking it to key hormonal pathways and in particular to abscisic acid (ABA; Németh et al, 1998;Bhalerao et al, 1999;Bradford et al, 2003;Radchuk et al, 2006;Baena-González et al, 2007;Lu et al, 2007;Rosnoblet et al, 2007;Ananieva et al, 2008;BaenaGonzález and Sheen, 2008;Lee et al, 2008;Jossier et al, 2009;Radchuk et al, 2010;Coello et al, 2012;Tsai and Gazzarrini, 2012). SnRK1 is a heterotrimeric complex composed of an a-catalytic subunit (SnRK1.1/1.2/1.3 in Arabidopsis) and two regulatory subunits, b and g (Polge and Thomas, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…During early grain development, SnRK1 was inactivated by T6P (Fig. 4), although SnRK1 was expressed in both endosperm and embryo throughout grain development (Coello et al 2012). Inactivation of SnRK1 may be necessary for carbon biosynthetic processes regulated by the amount of sucrose available; Subsequent development of the pericarp and embryo during grain filling is characterized by cessation of the inhibition of SnRK1 by T6P (O'Hara et al 2013).…”
Section: Regulation Of Grain Filling and Maturationmentioning
confidence: 98%
“…Moreover, Coello et al (2012) found a drastic decline in SnRK1 levels at 6 to 10 h after abscisic acid (ABA) treatment of wheat (Triticum aestivum) roots, but the total SnRK1 activity was weakly enhanced due to a simultaneous ABA-induced increase in phosphorylation/activation. If the woundinduced down-regulation of SnRK1 in the EFP is mediated by the well-known wound signal ABA remains to be investigated.…”
Section: Snf1-related Protein Kinases and The 14-3-3 32-kd Endonucleasementioning
confidence: 99%